PRACTICALITY ASSESSMENT DEVICE DEVELOPMENT OF LEARNING MODEL BASED METACOGNITIVE SKILL - Ijirana -; Suyono -; Sri Poedjiastoeti (PROSIDING SEMINAR KIMIA, 2015)
Practicality assessment device is developed according to PBKM model which has been rated valid by the experts. The aim of the research is to gain the valid PBKM model of the practility assessment device. The device consists of observation sheet of the applied model syntax, unit of learning program, and student’s worksheet. The valid score of the developed device is gained by giving the worksheet to five experts. The resultindicated that the whole evaluation aspects in the observation sheet of the applied model syntax which consist of direction to use the worksheet, the observation sheet content, and the used language gain the high score of validity. The validity of the whole evaluation aspects for the unit of learning program has been evaluated for high score by the experts, while the student’s activity sheet has been evaluated varies between high and very high. The result indicated the experts stated that the practicality score sheet which is developed from PBKM model is well-used in the implementation of PBKM model.